A Study to Assess the Knowledge and Practice of Self-Care Management Among Post-Operative Orthopaedic Patients in Selected Hospitals at K.G.F - Salini. S; Evangelin (International Journal of Orthopedic Nursing and Practices, 2025)
This study aimed to assess the level of knowledge and practice regarding self-care management among post-operative orthopedic patients using a non-experimental descriptive research design. A total of 60 post-operative orthopedic patients were selected through purposive sampling from a hospital in Kolar Gold Fields. Data were collected using a standardized checklist developed by Printz, Foster Kent, O’Leary, Robin, and Foster (1989), followed by an assessment of patients’ knowledge and practice related to self-care management. The findings revealed that a majority (61.7%) of the participants had inadequate knowledge, while 35% demonstrated moderate knowledge, and only 3.3% had adequate knowledge regarding self-care management. In contrast, the overall practice levels were more favorable: 93.7% of the patients exhibited adaptive self-care practices, whereas only 6.3% showed maladaptive practices. The correlation between knowledge and practice indicated a moderate positive relationship (r = 0.420), suggesting that higher knowledge levels were associated with better practice. Although the p-value (p = 0.601) was reported as statistically significant in the study context, it reflects the need for careful interpretation of statistical outcomes. Overall, the study highlights the gap between knowledge and practice and underscores the importance of strengthening patient education to improve self-care management among post-operative orthopedic patients.
Keywords: Knowledge; Orthopaedic; Post-Operative; Self-care; hospitals; practice